Impacts of cruise service quality and price on vacationers cruise experience: moderating role of price sensitivity - Chua, Bee Lia; Sanghyeop, Lee; Ben, Goh; Heesup, Han (Elsevier, 2015)
In view of the increased interest in cruise vacations and limited study on cruises, the purpose of this study was to shed light on an understanding of cruise vacationers’ evaluations of onboard experiences with cruise lines in North America and their loyalty-formation process. The empirical results revealed that interactional quality and outcome quality were significantly and positively associated with novelty and perceived value which in turn, affected satisfaction and loyalty. In addition, perceived price was a significant and negative predictor of perceived value. The moderating function of price sensitivity showed that novelty was more effective in inducing satisfaction in the low price sensitivity group and it was more effective in enhancing perceived value in the high price sensitivity group. Overall, these results help cruise line operators who observe that cruise vacationers have become more demanding on service quality, price, and value. Practical and theoretical contributions are discussed.